2013
DOI: 10.1063/1.4798472
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved measurements of charge carrier lifetimes in CdTe solar cells

Abstract: The lifetime of the minority charge carriers in polycrystalline Cadmium Telluride (pc-CdTe) for solar cell applications is a crucial material parameter and has been determined by analysis of the decay curves of the luminescence signal. Both the lateral and the transversal distributions of the carrier lifetime on the surface and in the bulk of pc-CdTe material as well as the respective solar cell characteristics were measured as a function of the deposition technique, the activation treatment, and the incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Luminescence techniques do though allow far greater extraction of additional spectroscopic information about GBs than either EBIC or scanning probe methods. Additional analysis has shown that carrier lifetime is reduced at the boundary [139] whilst recombination velocity is significantly increased [140], which Kanevce et al [141] link to V OC loss. Comparison with electron back scattered (EBSD) analysis also shows Σ3 twins are typically inert with little enhancement in recombination [142,144], presumably due to a lack of dangling bounds as posited by Consonni et al [148].…”
Section: Cathodoluminescence and Photoluminescencementioning
confidence: 92%
See 1 more Smart Citation
“…Luminescence techniques do though allow far greater extraction of additional spectroscopic information about GBs than either EBIC or scanning probe methods. Additional analysis has shown that carrier lifetime is reduced at the boundary [139] whilst recombination velocity is significantly increased [140], which Kanevce et al [141] link to V OC loss. Comparison with electron back scattered (EBSD) analysis also shows Σ3 twins are typically inert with little enhancement in recombination [142,144], presumably due to a lack of dangling bounds as posited by Consonni et al [148].…”
Section: Cathodoluminescence and Photoluminescencementioning
confidence: 92%
“…Surveying the CdTe grain boundary luminescence literature as a whole, two key points become apparent. Firstly, these techniques show an increase in non-radiative recombination at the GBs compared to GIs [60,[137][138][139][140][141][142][143][144][145][146] and secondly this recombination at GBs is significantly reduced following CdCl 2 treatment [138,139,143,144]. This is typically manifest through a reduction in observed exciton related luminescence at the GBs compared to GIs (see figure 10), with that reduction being minimised following CdCl 2 treatment.…”
Section: Cathodoluminescence and Photoluminescencementioning
confidence: 99%
“…Other systems, more accessible, implement one‐photon excitation. [ 17 ] However, for diffraction‐limited beam sizes (i.e., confocal mode), it is extremely challenging to achieve high optical resolution and remain in low injection for CIGS. A different—and complementary—approach is the use of wide‐field (or uniform) illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing efficient cadmium telluride (CdTe) solar cells with >21% power conversion efficiency requires postdeposition treatment with cadmium chloride (CdCl 2 ) . This treatment results in recrystallization of the CdTe layer, producing larger, more uniform grains. However, efficiency improvements cannot be attributed solely to microstructural changes because single-crystal CdTe exhibits poor photovoltaic performance and CdTe films deposited at high temperature show increased efficiency with CdCl 2 treatment despite minimal changes in grain size. , …”
Section: Introductionmentioning
confidence: 99%